Reassessment of Omalizumab-Dosing Strategies and Pharmacodynamics in Inner-City Children and Adolescents - Sorkness, Christine A. (J Allergy Clin Immunol Pract, 2013)
BACKGROUND: Treatment regimens for omalizumab are guided by a dosing table that is based on total serum IgE and body weight. Limited data exist about onset and offset of omalizumab efficacy in children and adolescents or subgroups that most benefit from treatment. OBJECTIVES: Post hoc analyses were conducted to (1) examine patient characteristics of those eligible and ineligible for omalizumab, (2) describe onset of effect after initiation of omalizumab and offset of treatment effect after stopping therapy, and (3) determine whether the efficacy differs by age, asthma severity, dosing regimen, and prespecified biomarkers. METHODS: Inner-city children and adolescents with persistent allergic asthma were enrolled in the Inner-City Anti-IgE Therapy for Asthma trial that compared omalizumab with placebo added to guidelines-based therapy for 60 weeks. RESULTS: Two hundred ninety-three of 889 participants (33%) clinically suitable for omalizumab were ineligible for dosing according to a modified dosing table specifying IgE level and body weight criteria. Baseline symptoms were comparable among those eligible and ineligible to receive omalizumab, but other characteristics (rate of health care utilization and skin test results) differed. The time of onset of omalizumab effect was <30 days and time of offset was between 30 and 120 days. No difference in efficacy was noted by age or asthma severity, but high exhaled nitric oxide, blood eosinophils, and body mass index predicted efficacy. CONCLUSIONS: A significant portion of children and adolescents particularly suited for omalizumab because of asthma severity status may be ineligible due to IgE >1300 IU/mL. Omalizumab reduced asthma symptoms and exacerbations rapidly; features associated with efficacy can be identified to guide patient selection.